2009
DOI: 10.3797/scipharm.0906-03
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis and Standardization of Arjunarishta – An Ayurvedic Cardioprotective Formulation

Abstract: Arjunarishta (Parthadyarishta) is an important Ayurvedic formulation used for cardiovascular disorders and is prepared by fermenting the decoction of specified plant materials using flowers of Woodfordia fruticosa. In present communication, an HPLC-PDA method was developed for the standardization of Arjunarishta by quantitative estimation of major antioxidant compounds, ellagic acid, gallic acid, ethyl gallate, quercetin and kaempferol as markers. The developed method was validated with respect to linearity, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Lal et al [34] reported an HPLC-PDA-based standardization method for this formulation, utilizing more than one marker compound. It is prepared by fermenting the decoction of the bark of Terminalia arjuna, fruits of Vitis vinifera, and flowers of Madhuca indica using flowers of Woodfordia fruticosa.…”
Section: Arjunarishtamentioning
confidence: 99%
“…Lal et al [34] reported an HPLC-PDA-based standardization method for this formulation, utilizing more than one marker compound. It is prepared by fermenting the decoction of the bark of Terminalia arjuna, fruits of Vitis vinifera, and flowers of Madhuca indica using flowers of Woodfordia fruticosa.…”
Section: Arjunarishtamentioning
confidence: 99%
“…It was already reported in literature that several factors such as generation of acid and alcohol during fermentation of decoction stimulate the hydrolysis of the process, thus causing biotransformation of chemical substances. [13,14] Various reports have been published which explained the degradation pattern of polyphenolics substances during fermentation. [15] Publication of these data promoted us to explore the effect of fermentation on chemical changes in V. vinifera fruits.…”
Section: Original Articlementioning
confidence: 99%
“…2C). Structure of EG was further validated by comparing the spectral data from earlier studies (He et al, 2008;Lal et al, 2009).…”
Section: Characterization Of Hplc Peakmentioning
confidence: 99%